PENDIDIKAN ISLAM WASATHIYAH: MELAWAN ARUS PEMIKIRAN TAKFIRI DI NUSANTARA - FITRI, AGUS ZAENUL (LPPM IAIN Parepare, 2015)
Wasathiyah Islam emerged as a counterweight of the emergence of a group that often and another group (takfris). In addition, education also wasathiyah moderate understanding of Islam, with the idea of opposing violence, defend the oppressed, fanaticism, ekterimisme, reject intimidation, and terrorism. Wasathiyah (moderation) including the main Islamic character; because this value always connect Muslims with their basic principles. Their current living conditions are not disconnected from their past history and strongly connected with the history of the lives of the righteous generation earlier. In the view of Islam, life is always changing and rotation. Therefore, the attitude of moderate Islam refused to part of the present and ignore the events that occur in it. Islam also rejects wrap moderation ijtihad which is affected by a condition or environment with the clothes of immortality and maintenance of errors and changes, without any other ijtihad which is also inï¬‚uenced by the environment and the environmental conditions that are different from the previous ijtihad.